Polycystic parotid disease (polycystic sclerosing adenosis associated with dysgenetic polycystic disease): Case report. - Cabanillas-Lapa, José Luis (2023)
Introduction: Polycystic sclerosing adenosis / adenoma (SPA) is accepted as a very rare new benign neoplastic entity of the salivary glands that generally involves the parotid gland. Dysgenetic polycystic disease is another rare entity with histology similar to SPA and that also affects the parotid gland more frequently. Case report: The case of a 28-year-old woman with increased volume of the right parotid gland of approximately 3 years of evolution is presented, whose histopathological analysis suggested the diagnosis of Polycystic Sclerosing Adenosis / adenoma associated with Polycystic Dysgenetic Disease of the right parotid gland. The patient received surgical treatment of total parotidectomy with preservation of the facial nerve. At the moment with remission of the disease.